The Percentage of Dietary Phosphorus Excreted in the Urine Varies by Dietary Pattern in a Randomized Feeding Study in Adults - McClure, Scott T (J Nutr, 2019)
BACKGROUND: Urinary phosphorus excretion has been proposed as a recovery biomarker of dietary phosphorus intake. However, it is unclear whether phosphorus excretion is constant across a range of dietary and nondietary factors. OBJECTIVE: We assessed whether percentage urinary phosphorus excretion is constant across 3 dietary patterns in the Dietary Approaches to Stop Hypertension (DASH) trial. METHODS: DASH is a completed feeding study of 459 prehypertensive and stage 1 hypertensive adults (52% male, 56% black). After a 3-wk run-in on a typical American (control) diet, participants were randomly assigned to the control diet, a diet rich in fruits and vegetables (FV diet), or a diet rich in fruits, vegetables, and low-fat dairy with reduced saturated fat and cholesterol (DASH diet) for 8 wk. We estimated the percentage phosphorus excretion as urinary phosphorus excretion (from 24 h urine) divided by phosphorus intake (from analyzed food composites). Differences between group means for all 3 diets were compared by ANOVA followed by pairwise comparisons with Tukey's honest significant difference test. RESULTS: At the end of the intervention, the mean phosphorus intake was 1176 mg/d (95% CI: 1119, 1233 mg/d), 1408 mg/d (1352, 1464 mg/d), and 2051 mg/d (1994, 2107 mg/d) in the control, FV, and DASH diet, respectively (P < 0.001, all comparisons). The mean phosphorus excretion was 734 mg/d (682, 787 mg/d), 705 mg/d (654, 756 mg/d), and 872 mg/d (820, 923 mg/d) in the control, FV, and DASH diet, respectively (P = 0.74 control vs. FV, P < 0.001 all other comparisons). The mean percentage phosphorus excretion was 63% (60%, 67%), 51% (48%, 54%), and 43% (39%, 46%) in the control, FV, and DASH diet, respectively (P < 0.001, all comparisons). CONCLUSIONS: These findings in prehypertensive and stage 1 hypertensive adults strongly suggest that urinary phosphorus excretion should not be used as a recovery biomarker for dietary phosphorus intake, given the wide range of urinary phosphorus excretion across dietary patterns. This trial is registered at clinicaltrials.gov as NCT0000054.